Effect Of Work Stress and Leadership Style on Employee Performance PT. Cakra Guna Cipta Wagir, Malang Regency - Muchamad Muslih; Aldy Rostyawan (JOB: Journal of Organizational Behavior, 2025)
This study aims to determine and analyze the effect of work stress and leadership style on employee performance at PT. Cakra Guna Cipta Wagir Kab. Malang. The population in this study were 70 people, the sample used was 41 people. Data collection techniques used in this study were observation, documentation and questionnaires. The method of analysis in this study is a quantitative method. The data analysis technique used in this study is multiple linear regression using the SPSS version for windows program. The results of this study indicate that the first partially work stress has a significant effect on employee performance. Second, partially the leadership style has no significant effect on employee performance. Third, simultaneously work stress and leadership style have a significant effect on employee performance.